Viterbi-based estimation for Markov switching GARCH model - Elliott, Robert J., author; Lau, John W., author; Miao, Hong, author; Kuen Siu, Tak, author; Applied Mathematical Finance, publisher (Colorado State University. Libraries, 2011)
We outline a two-stage estimation method for a Markov-switching Generalized Autoregressive Conditional Heteroscedastic (GARCH) model modulated by a hidden Markov chain. The first stage involves the estimation of a hidden Markov chain using the Vitberi algorithm given the model parameters. The second stage uses the maximum likelihood method to estimate the model parameters given the estimated hidden Markov chain. Applications to financial risk management are discussed through simulated data.
Published as: Applied Mathematical Finance, vol.19, no. 3, pp.219-231, July 2012, https://doi.org/10.1080/1350486X.2011.620396.
Keywords: volatility; regime switching; GARCH; Viterbi algorithm; reference probability; filter; maximum likelihood estimation; value at risk